Italian National Forest Inventory-Methods and Results of the Third Survey Inventario Nazionale delle Foreste e dei Serbatoi Forestali di Carbonio-Metodi e Risultati della Terza Indagine - Gasparini, Patrizia; Di Cosmo, Lucio; Floris, Antonio; De Laurentis, Davide (Springer Tracts in Civil Engineering, 2022)
This open access book deals with the methods and the results of the third Italian national forest inventory (INFC2015). Arma dei Carabinieri is entrusted with the realisation of the National Forest Inventory and with the decisions about the aims of the survey and data treatment. National forest inventories produce statistically based information on forests over country areas. Such information is used either at subnational or at supranational level in a great number of spheres and processes, included possibility to depict the status of the world forests. Italy conducted its first forest inventory in 1985 and in 2001 a permanent national forest inventory was launched to have periodically updated statistics. Due to the growing concern about the environment and especially the climate change, estimating forests carbon pools was a stated main objective and it was accordingly named Italian National Inventory of Forest and Forest Carbon Pools (INFC). The book begins with a description of the general organisation, the definitions, the methods and the estimation procedures. It proceeds showing the main estimates produced by INFC2015, in tables that are given in the book chapters. The estimates are presented through texts that introduce the subject matter, explain the way the related variables were surveyed and comment on the main outcomes with the help of graphics. The estimates presented include forest area, management and production, biodiversity and protection, forest health, protective and socio-economics functions. Role of forest in the carbon balance was analysed in a specific Chapter, as this is important for its role in the climate change mitigation. The book ends providing an understanding of the current dynamics of Italian forests by comparing the estimates obtained from INFC2005 and INFC2015, the last two national surveys.